PERUBAHAN PARADIGMA KEILMUAN IAIN MENUJU UIN AR-RANIRY - Syamsul Bahri (Islam Futura, 2012)
Islamic education Institution, which is an integrated part of National education system, also faces the globalization phenomenon. So it is expected to prepare for it. On the other hand, the basic problem faced by the Islamic education Institution is that the paradigm of Islamic knowledge itself, in which Islamic knowledge and general knowledge are two different things. Originally, Islam does not recognize the split knowledge, all in more applicative ways. For example, the efforts of some Islamic Higher Education Institutions toward Islamic university. The idea of Islamic University introduced by knowledge which is useful for human beings are to be considered important. In this new millennium, the idea of integrating knowledge becomes increasingly popular Islamic scholars in Indonesia is the right choice in facing the globalization era.